FINANCING COMPANIES IN THE CONTEXT OF ECONOMIC SLOWDOWN AND SANCTIONS - M. V. Petrov (Финансы: теория и практика, 2018)
The article analyzes the current trends of financing Russian non-financial companies, formed in the mid‑2010- is during the slowdown of the growth of the national economy, the reduction of foreign capital inflows and the introduction of anti-Russian sanctions.The purpose of the study is to analyze changes in the dynamics and structure of sources of financing of domestic companies that occurred in 2014–2017, as well as to assess possible measures to expand the availability of financial resources for them.We used general scientific methods of statistical analysis, scientific abstraction and logical generalization, as well as comparative and institutional approaches.The paper considers the dynamics and peculiarities of financing of Russian companies in 2014–2017. We established that despite the compression of foreign capital inflow that occurred in the specified period, the enterprises were able to largely compensate losses increasing borrowings from domestic banks and the corporate bond market, as well as obtaining financial support from the state in the framework of anti-crisis measures.The replacement of foreign financing with domestic sources allowed to maintain the stability of the corporate sector during the crisis period. However, today, when the economy is out of crisis and enterprises to need additional funds for business development, they face a limited supply of financial resources in the domestic market, mainly due to the sharp slowdown in the dynamics of bank lending to the real sector, observed since 2015.We conclude that in the conditions of reduction of capital imports the main reserve for increasing the availability of financial resources for the Russian enterprises is the increase of bank lending to the economy. In order to encourage it, the state should actively expand the practice of public-private partnership mechanisms in the financial and banking sector, including the provision of guarantees for loans and joint financing with banks of priority investment projects.